(untitled) (Ta’limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2024)
This article analyzes the concepts of real and fictional time and their expression in works of art with various linguistic units, as well as the role they play in the process of analyzing the work. The article also argues that through the artisticexpression of the concepts of time and space in a work of art, the writer shows the reader a deeper understanding of the inner world of the characters and expands the thematic meaning of the work.